ANALYSIS OF THE IMPACT OF RISK MANAGEMENT STRATEGIES ON THE FINANCIAL PERFORMANCE OF THE BUDI KARYA MAJU COMPANY - Budiyono Budiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to analyze the impact of risk management strategies on the financial performance of the Budi Karya Maju company. This research involves collecting secondary data from company financial reports over the last five years period and in-depth analysis of the risk management strategies implemented by the company. The multiple linear regression analysis method is used to identify the relationship between independent variables, namely risk management strategies (such as risk diversification, insurance, hedging and other risk mitigation), with the dependent variable, namely the company's financial performance (such as sales growth, profitability and liquidity). The research results show that the implementation of risk management strategies has a significant impact on the financial performance of the Budi Karya Maju company. Risk and insurance diversification has been proven to have a significant positive influence on sales growth and company profitability. On the other hand, risk mitigation practices also contribute positively to company liquidity. However, the analysis results also show that the use of hedging techniques does not have a significant impact on the company's financial performance. These findings provide valuable insights for company management in optimizing their risk management strategies to improve financial performance. The practical implication of this research is the importance of considering risk diversification and insurance as the main strategy, while still paying attention to risk mitigation practices to ensure optimal liquidity. For future researchers, it is recommended to expand this research by considering external factors, such as market conditions and industry regulations, to gain a more comprehensive understanding of the relationship between risk management and company performance. Keywords: Risk Management, Financial Performance, Risk Management Strategy